Low-temperature thermodynamics of Xe-doped fullerite C60 - Klochko, M.S.; Strzhemechny, M.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2015)
Using a model of the fullerene C60 molecule with carbon atoms uniformly distributed over its surface, the potential energy U(n) of a Xe atom in an octahedral void of C60 is calculated. Within the framework of three-dimensional harmonic oscillator, the lowest energy levels are estimated and the contribution of xenon impurity atoms to the heat capacity of the Xe–C60 system is determined. The contribution of Xe dopants to the total heat capacity is shown to be essential compared to that of pure fullerite. Using the calculated energy spectrum we estimated the contribution of Xe atoms to the thermal expansivity of C60 with 37% of Xe. This contribution is in a qualitative agreement with experimental findings. We estimated the Grüneisen parameter Г due to the anisotropic part of U(n) to show that the negative part of Г is negligible due to the very small width of the five lower oscillatory wave functions.